Diseño de un relleno sanitario y planta segregadora de residuos sólidos urbanos para el distrito de Santiago de Chuco - La Libertad 2018 - Esquivel Zavala, Leonardo Ronald (2019)
The main objective of this project is to design a sanitary landfill and a segregation plant for a sanitary, reaproveable and environmentally safe final disposal of solid waste from the urban area of the district of Santiago de Chuco - La Libertad. This study is very important to improve the integral management of municipal solid waste and above all to maintain the quality of the environment. Ensuring a recovery of municipal solid waste and increasing the useful life of the landfill. The study began with extensive research through bibliographic data and satellite images of the area of influence of the project. Among these documents, its topography, hydrogeology, geology, population and demographic statistical data were mainly investigated. On the other hand, basic studies were carried out, such as evaluation of the integral management of municipal solid waste, characterization study, referential study of the site and an identification, evaluation and mitigation of the possible environmental impacts of the project. Once the previous studies were completed, the sanitary landfill and the segregation plant were designed, obtaining as a result that for their management they will be manually, using the trench or trench method, with a total area for the landfill of 14407 m2, 1.5 hectares, with 29 ditches. The segregation plant itself will consist of three areas (reception and classification area, organic waste storage area and inorganic waste storage area), with dimensions of 68 m2, 1724 m2 and 264 m2 respectively